Puzzling choices in hard times: Union ideologies of social concertation in the Great Recession - Arianna Tassinari; Jimmy Donaghey; Manuela Galetto (Industrial Relations: A Journal of Economy and Society, 2021)
Using the cases of Ireland and Portugal during the post-2008 Great Recession, we argue that unions' ideological formations around social concertation are central in aiding them to navigate their options about whether to engage in concessionary bargaining with government under crisis conditions. Building on Hyman's triangle of union identity, we show how an ideational perspective can complement interest-based accounts of unions' strategies to explain their engagement with policymakers or their opposition in the macro-management of the economy.
Keywords: 330